Measurement Bias of Polyp Size at Colonoscopy. Issue 9 (September 2017) - Sakata, Shinichiro; Klein, Kerenaftali; Stevenson, Andrew R. L.; Hewett, David G.
Abstract : BACKGROUND: The success of current and proposed strategies to reduce colorectal cancer (CRC) incidence and mortality rates are fundamentally based on measurement accuracy. OBJECTIVE: The aim of this study was to evaluate the densities of colorectal polyps individually measured at colonoscopy and whether measurement bias is a systemic phenomenon among colonoscopists. DESIGN: A population-wide, observational study. SETTING: All hospitals of the government-funded health system in Brisbane, Australia. PATIENTS: Our study investigated measurement bias at colonoscopy through systematic analysis of 8, 591 individual polyp measurements recorded from 12, 597 colonoscopies. All colonoscopies performed over a 12-month period between December 1, 2014, and November 30, 2015, were included. RESULTS: A total of 12, 597 electronic colonoscopy reports were individually reviewed, hospital-by-hospital, and 8, 591 individual size measurements from 18, 276 detected polyps (47%) were obtained. LIMITATIONS: Our study is limited because the true size of unresected polyps was unknown. We chose not to compare pathologic and histologic sizes as resection specimens sent to pathologists are morphologically different and are measured differently to the pre-resection polyp images seen by endoscopists. CONCLUSIONS: Colonoscopists may be inaccurate in the measurement of polyp size and appear biased towards and against certain size measurements. These findings cast doubt over the validity of international post-polypectomy surveillance guidelines and the safety of optical diagnosis as a potential management paradigm for diminutive colorectal polyps. They also question the historical accuracy of polyp size data and risk estimates upon which these strategies were based.